Siklus Hidup dan Morfologi Nematoda Sista Kentang (Globodera rostochiensis) - Iis Nur Asyiah (Universitas Syiah Kuala, 2009)
Observation had been conducted for life cycle and morphology of Nematoda Sista Kentang (NSK).The result shows J2 has been found in the day-eight, whereas J3 and J4 was found in the day 20 to 32 after the plant budding. Female J4 has bottle shape and matured has swollen shape. Mature female Nematode has golden color and is called Golden Nematode. Male nematode formed worm. Both male and female nematodes were found in the day-forty after budding. The amount of eggs are around 300 to 600 depending on cyst size. Cyst has been found in the day-fifty six after budding.